Pengaruh Dakwah Mentoring Rohani Islam (ROHIS) Terhadap Pembentukan Akhlak Siswa SMA Negeri 1 Tebing Tinggi - Fajar Ahmad Lazuardy (Bashirah, 2024)
This research aims to empirically test the influence of Islamic spiritual mentoring preaching on the moral formation of students at SMA Negeri 1 Tebing Tinggi. The population in this study was 179 people. The sample used in this research was all members of Rohani Islam class X and XI, totaling 40 people. The sample collection technique was through proportionate stratified random sampling. Data was collected through questionnaires distributed to 40 respondents. The statistical method uses the product moment formula. To facilitate analysis, use the SPSS version 26 application. Based on the hypothesis, Rohis' mentoring preaching influences the moral formation of students at SMA Negeri 1 TebingTinggi, which means Ha is accepted and Ho is rejected. The results of this research show that there is a significant influence between Islamic spiritual mentoring preaching on the moral formation of students at SMA Negeri 1 Tebing Tinggi. The coefficient value in the research was 0.800. The magnitude of the influence was 64% and the other 36% was influenced by other factors not examined in this study.